Pain prediction by serum biomarkers of bone turnover in people with knee osteoarthritis: an observational study of TRAcP5b and cathepsin K in OA - Nwosu, Lilian Ngozi; Allen, Maximillian; Wyatt, L.A.; Huebner, J.L.; Chapman, Victoria; Walsh, David A.; Kraus, Virginia (Elsevier, 2017)
Objectives: To investigate serum biomarkers, tartrate resistant acid phosphatase 5b (TRAcP5b) and cathepsin K, indicative of osteoclastic bone resorption, and their relationship to pain and pain change in knee osteoarthritis (OA). Methods: Sera and clinical data were collected from 129 people (97 with 3-year follow-up) with knee OA from the Prediction of Osteoarthritis Progression (POP) cohort. Knee OA-related outcomes in POP included: WOMAC pain, NHANES I (pain, aching and stiffness), subchondral sclerosis, and radiographically determined tibiofemoral and patellofemoral OA. Two putative osteoclast biomarkers were measured in sera: TRAcP5b and cathepsin K. Medial tibia plateaux were donated at knee arthroplasty for symptomatic OA (n=84) or from 16 post mortem controls from the Arthritis Research UK (ARUK) Pain Centre joint tissue repository. Osteoclasts were stained for TRAcP within the subchondral bone of the medial tibia plateaux. Results: Serum TRAcP5b activity, but not cathepsin K-immunoreactivity, was associated with density of TRAcP-positive osteoclasts in the subchondral bone of medial tibia plateaux. TRAcP-positive osteoclasts were more abundant in people with symptomatic OA compared to controls. Serum TRAcP5b activity was associated with baseline pain and pain change. Conclusions: Our observations support a role for subchondral osteoclast activity in the generation of OA pain. Serum TRAcP5b might be a clinically relevant biomarker of disease activity in OA.